1997
DOI: 10.1002/jor.1100150316
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of cytokines and their receptors in adhesive capsulitis of the shoulder

Abstract: The purpose of this study was to test the hypothesis that specific cytokines are involved in the initiation and evolution of the fibrotic process in adhesive capsulitis of the shoulder. After approval from the Institutional Review Board, biopsies of shoulder capsule and synovium were collected during shoulder arthroscopy from 19 patients with adhesive capsulitis, 14 patients with nonspecific synovitis and no fibrosis or clinical evidence of adhesive capsulitis, and seven patients undergoing surgery for another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
229
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(248 citation statements)
references
References 18 publications
(1 reference statement)
8
229
0
5
Order By: Relevance
“…The inflammatory process is considered another pathogenesis of adhesive capsulitis. Rodeo et al found elevated levels of pro-inflammatory cytokines in adhesive capsulitis patients14. They proposed that the stimulation of inflammation caused by cytokines can engender shoulder synovitis, and this can result in a fibrotic cascade that is associated with growth factors such as TGF-beta14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory process is considered another pathogenesis of adhesive capsulitis. Rodeo et al found elevated levels of pro-inflammatory cytokines in adhesive capsulitis patients14. They proposed that the stimulation of inflammation caused by cytokines can engender shoulder synovitis, and this can result in a fibrotic cascade that is associated with growth factors such as TGF-beta14.…”
Section: Discussionmentioning
confidence: 99%
“…Rodeo et al found elevated levels of pro-inflammatory cytokines in adhesive capsulitis patients14. They proposed that the stimulation of inflammation caused by cytokines can engender shoulder synovitis, and this can result in a fibrotic cascade that is associated with growth factors such as TGF-beta14. The chronic fibrosis process of capsulitis is confirmed by observing the histologic presentation of fibroblast cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated cytokine levels appear predominately involved in the cellular mechanisms of sustained inflammation and fibrosis in primary and some secondary frozen shoulder. 19,49,75,101 Although the initial stimulus is unknown, Bunker et al 19 Frozen shoulder is typically considered an inflammatory process; however, this concept is being challenged. No significant inflammatory cells in the capsular tissue have been identified upon histological examination.…”
Section: Level 5 J Orthop Sportsmentioning
confidence: 99%
“…100 Although the precise etiology remains unclear, recent evidence identifies elevated serum cytokine levels as part of the process. 19,49,101 Cytokines and other growth factors facilitate tissue repair and remodeling as part of the inflammatory process. Elevated cytokine levels appear predominately involved in the cellular mechanisms of sustained inflammation and fibrosis in primary and some secondary frozen shoulder.…”
mentioning
confidence: 99%
See 1 more Smart Citation